SENSORY MARKETING: EVIDENCE FROM A CLUSTER ANALYSIS OF GERMAN CONSUMERS - Sidali, Katia Laura; Obermowe, Tim; Filaretova, Olga; Spiller, Achim (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708811 In the consumer behaviour literature regarding food consumption the food-related lifestyle (FRL) approach conceived by Grunert et al. (1993) is a well-established tool to target groups based onlifestyle and dietary habits. On the contrary, studies attempting to identify consumer groups according to their sensory preferences are rather scarce. In this article, we present an approach that combines elements of the FRL approach with variables of sensory perception of food. The findings show that it is meaningful to build a consumer typology based on both food-related lifestyle variables and sensory preferences. The six clusters resulting from this study differ significantly from each other so that managerial recommendations are derived.